A CLINICOPATHOLOGICAL STUDY OF ALLERGIC RHINITIS - Bellamkonda, Mahita; g, VinodKumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: Allergic rhinitis (AR) is on the rise in our society for various reasons. It is said that allergy might represent a primary or secondary factor in up to half the patients encountered in an otolaryngology practice. Thus, the management of AR constitutes a large proportion of the day-to-day practice. In addition to its primary effect, inhalant allergy of the upper respiratory tract might affect the development and clinical course of other disease states such as sinusitis, otitis media, and asthma due to the mucosal continuity. Hence, this study was conducted to know the comorbid associations of AR and also the pathology in inferior turbinate hypertrophy (ITH). Methods: A time-bound, descriptive cross-sectional study was conducted in ENT OPD. Patients were selected for the study after proper history taking, clinical examination, laboratory investigations such as absolute eosinophil count (AEC) and diagnostic nasal endoscopy, and consent for biopsy from inferior turbinate and histopathological examination using predefined inclusion and exclusion criteria. Nasal symptoms of sneezing, rhinorrhea, nasal pruritus, nasal obstruction, anosmia and non-nasal symptoms of eye itching, watering, foreign body sensation, and pharyngeal itching were recorded. Results: The mean age of the patients was 27.08 years with a standard deviation of 6.1. Patients were clinically evaluated regarding symptoms in ear, nose, throat, eyes, and respiratory system. All patients had nasal symptoms whereas 53.34% patients had ophthalmic and pharyngeal symptoms. Aural comorbidity was most common with complaints in 68.33% followed by respiratory symptoms in 30% patients. About 40% patients complained of sleep disturbances. Nearly 31.67% patients had a positive family history. The pale nasal mucosa was seen in 63.33% patients. Almost 70% patients had intermittent AR, of which 43.33% had a mild degree. About 55% cases had AEC <350 cells/cumm. Almost 51.67% patients had more than five eosinophils per high power field in the biopsy of their inferior turbinates. Conclusion: Although most patients presented with nasal symptoms, ophthalmic and pharyngeal symptoms were commonly presented. ITH with pale nasal mucosa were the most common examination findings. Although AEC was not raised in most of the patients, more than half patients had a raised eosinophil count in the inferior turbinate biopsy. Thus, in a patient with AR, special attention has to be given to the ear, throat, eye, and asthmatic aspect. Eosinophil count in inferior turbinate biopsy is fairly reliable indicator in allergic turbinates. Keywords: Allegic rhinitis, Asthma, Absolute eosinophil count, Eosinophil count, Inferior turbinate biopsy.